Pemanfaatan API Youtube dalam Pengembangan Aplikasi Portal Video Penangkaran Kenari untuk Peternak Kenari Berbasis Android - Edwin Yosef Setiawan Sihombing; Tibyani Tibyani; Buce Trias Hanggara (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Indonesia's economic growth grew by 5.05%, this growth was recorded in the calculation of the Badan Pusat Statistik (BPS) Indonesia in the second quarter of 2019. UMKM has became one of the drivers of Indonesia's economic growth. The popular UMKM in East Java is walnut cattle. An ongoing and continuous learning process is important to continue developing the walnut cattle business and the quality of the results of canary breeding. Learning media that can provide all forms, ranging from visuals and audio is the internet. The internet platform used as a learning medium for canary breeding is YouTube. In this study to make it easier for canary breeders to use YouTube, the author developed an Android-based application using the youtube API to help display videos containing information about canary breeding, and also to support video search and channel search features. This application was designed using the waterfall method. Testing is done by black-box testing method for system testing and beta testing. The result of black-box testing is a system that is built to run according to expectations, and the results of beta testing are applications that are built to be easily understood, have accurate information and meet the needs of canary breeders.